The Influence of Digital Marketing and Brand Awareness on Increasing Brand Image and its Impact on Purchasing Decisions - Oktavia Mulyani; Nurul Hermina (IKIP Mataram, 2023)
The current beverage product that is trending in Solo city is cheese tea. This product is a blend of the and the cheese. And lucky cheese tea is one of the brands present in the city of Solo. This study aims to test and analyze whether there is an influence of digital marketing and brand awareness on increasing brand image and the impact on purchasing decisions of cheese tea products in solo cities. This research was conducted on Lucky Cheese Tea consumers spread across the city of Solo, with a total sample of 154 respondents. The research method uses a descriptive and verifiable approach. The analysis technique uses Structural Equation Modeling with SmartPls 3.3.9 software. The findings in this study show that: digital marketing and brand awareness have a significant influence on brand image, while digital marketing, brand awareness and brand image have a significant influence on Purchasing Decisions. If digital marketing and brand awareness have been carried out optimally, it will be positively embedded in the eyes of consumers of the product and what needs to be done is to maintain a good brand image to achieve maximum purchasing decisions.